Analisis Peran Badan Permusyawaratan Desa di Desa Banjar Lopak Kecamatan Benai Kabupaten Kuantan Singingi - Lestari, Nopia; Suryanef, Suryanef; Hasrul, Hasrul; Bakhtiar, Yusnanik (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
he Village Consultative Body (Badan Permusyawaratan Desa or BPD) acts as a mediator between the community and the village government, primarily tasked with accommodating and channeling community aspirations. This study examines the effectiveness of the BPD in fulfilling this function in Banjar Lopak Village, Kuantan Singingi Regency, and identifies the challenges faced by the institution. Using a qualitative descriptive approach, data were collected through interviews with the village head and BPD members and analyzed using triangulation techniques to ensure validity. Findings reveal that the BPD has not effectively performed its role due to limited human resource capacity. Many members lack understanding of their duties, resulting in unmet community aspirations and dissatisfaction. The study is limited to Banjar Lopak Village, with potential biases from qualitative methods. Future research could explore multiple villages and employ mixed-methods to provide broader and more comprehensive insights.